Análise, modelagem e controle de um conversor CC-CC, não isolado, elevador entrelaçado - abaixador, para conexão de sistemas fotovoltaicos na rede monofásica - Taconelli, Mauricio (Universidade Federal de São Carlos, 2021)
The increasing incorporation of alternative energy sources into the electrical system, despite its advantages, raises a wide range of new challenges, and it is in this context that power electronics devices start to play a fundamental role. Based on this consideration, this dissertation analyzed a model of DC-DC converter derived from the Interleaved Boost converter cascaded with Buck converter which can operate as step-up or as step-down converter for applications in photovoltaic grid-tie systems through a unfolding inverter. Thus, the principles of operation, circuit configuration and modeling in state space of the converter will be presented for each mode of operation. Subsequently, the methodology for dimensioning the passive elements is presented and, then, analyzes related to the influence of the losses of these elements on the converter gain are performed. Thereafter, the control architecture for the system connected to the power grid was designed based on the concept of time-sharing and, therefore, only one of the high frequency stages of the operation at a time. Finally, simulations are carried out, for different operating scenarios, with the objective of verifying performance and validating the proposed theoretical model.
Analysis, modeling and control of a DC-DC converter, nonisolated, interleaved step-up - step-down, for single-phase grid-connected photovoltaic systems
Keywords: Conversores CC-CC; Conversor elevador entrelaçado; Conversor abaixador; Eletrônica de potência; Energia fotovoltaica; Fontes alternativas de energia.; Geração distribuída de energia; Inversor conectado à rede; DC-DC converters; Boost interleaved converter; Buck converter; Power electronics; Photovoltaic energy; Alternative sources of energy; Distributed generation; Grid tie inverter; ENGENHARIAS::ENGENHARIA ELETRICA::CIRCUITOS ELETRICOS, MAGNETICOS E ELETRONICOS; ENGENHARIAS::ENGENHARIA ELETRICA::SISTEMAS ELETRICOS DE POTENCIA